2013
DOI: 10.1089/apc.2012.0416
|View full text |Cite
|
Sign up to set email alerts
|

Serodiscordance and Disclosure Among HIV-Positive Pregnant Women in the Southwestern United States

Abstract: The prevalence of HIV-positive pregnant women in relationships with HIV-negative men in the United States is unclear. The purpose of this study was to calculate the prevalence of HIV-positive pregnant women with a serodiscordant (HIV-negative) partner within a single clinic population, assess disclosure of their HIV status, and examine factors associated with disclosure. All HIV-positive pregnant women who received prenatal care at the Harris County Hospital District Women's Program at Northwest Health Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…This supports some previous research which has suggested that the quality of the relationship plays a role in disclosure outcomes [e.g. [27][28][29]. This study is the first to draw multiple links between the quality of the relationship and widespread disclosure outcome and it suggests the need for more research in this area.…”
Section: Discussionsupporting
confidence: 89%
“…This supports some previous research which has suggested that the quality of the relationship plays a role in disclosure outcomes [e.g. [27][28][29]. This study is the first to draw multiple links between the quality of the relationship and widespread disclosure outcome and it suggests the need for more research in this area.…”
Section: Discussionsupporting
confidence: 89%
“…Confiding in religious leaders was more reported than in a work colleague/employer. This represents the evaluation of the choice to disclose to whom they think could provide support and this is consistent with other studies from around the world [41][42][43][44][45]48].…”
Section: Discussionsupporting
confidence: 87%
“…26 In our study, 46% of the participants did not know the HIV-status of their male partner and 28% presumed their partners were HIV-uninfected. Most women reported disclosure of HIV status to their partners, but 26% of participants reported that some or none other their partners knew their HIV status.…”
Section: Discussionmentioning
confidence: 59%